National consensus quality indicators to assess quality of care for active surveillance in low-risk prostate cancer: An evidence-informed, modified Delphi survey of Canadian urologists/radiation oncologists - Timilshina, Narhari; Finelli, Antonio; Tomlinson, George. Tomlinson; Gagliardi , Anna; Sander , Beate; Alibhai, Shabbir M.H. (Canadian Urological Association Journal, 2021)
Introduction: Although many low-risk prostate cancer (PCa) patients worldwide currently receive active surveillance (AS), adherence to clinical guidelines on AS and variations in care at the population level remain poorly understood. We sought to develop system-level quality indicators (QIs) and performance measures for benchmarking the quality of care during AS. Methods: Convenience sampling methods were used to identify an expert panel among practicing urologists and radiation oncologists across Canada. QI development involved two phases: 1) proposed QIs were identified through a literature search and published clinical guidelines on AS; and 2) indicators were selected through a modified Delphi process during which each panelist independently rated each indicator based on clinical importance. QI items were chosen as appropriate measures for quality of AS care if they met prespecified criteria (disagreement index <1 and median importance of ≥7 on a nine-point scale). Results: Among 42 invited expert panel members, the response rate was 45% (n=19). Expert panel members were well-represented by type of physician (84% urologists, 16% radiation oncologists) and practice setting (79% academic, 21% non-academic). The expert panel endorsed 20 of 27 potential indicators as appropriate for measuring quality of AS care. Conclusions: We developed a set of QIs to measure AS care using published guidelines and clinical experts. Use of the indicators will be assessed for feasibility in healthcare databases. Reporting quality of care with these AS indicators may enhance adherence, reduce variation in care, and improve patient outcomes among low-risk PCa patients on AS.